2004
DOI: 10.1113/jphysiol.2003.057133
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of arterial baroreflex dynamic response during mild orthostatic stress in humans

Abstract: We tested the hypothesis that in humans, carotid-baroreflex dynamic responses (evaluated by examining the time course of the carotid-baroreflex-induced alterations in muscle sympathetic nerve activity (MSNA), mean arterial blood pressure (MAP) and heart rate (HR)) would be altered during mild orthostatic stress in ways that serve to limit orthostatic hypotension. In 12 healthy subjects (10 male, 2 female), 5-s periods of neck pressure (NP) (50 mmHg) and neck suction (NS) (− 60 mmHg) were used to evaluate carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 41 publications
3
21
0
1
Order By: Relevance
“…Furthermore, previous studies have demonstrated an increase of sympathetic baroreflex sensitivity during mild levels of LBNP (11,15). The increased sympathetic baroreflex sensitivities observed during LBNP in the present study and others (11,15) are suggestive that alterations of sympathetic baroreflex sensitivity during orthostatic stress are important in the maintenance of orthostatic tolerance. Our results indicate that such adjustments are not different between the EF and ML phases of the menstrual cycle.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, previous studies have demonstrated an increase of sympathetic baroreflex sensitivity during mild levels of LBNP (11,15). The increased sympathetic baroreflex sensitivities observed during LBNP in the present study and others (11,15) are suggestive that alterations of sympathetic baroreflex sensitivity during orthostatic stress are important in the maintenance of orthostatic tolerance. Our results indicate that such adjustments are not different between the EF and ML phases of the menstrual cycle.…”
Section: Discussionsupporting
confidence: 61%
“…Nevertheless, our data indicate an increase of sympathetic baroreflex sensitivity during progressive LBNP that was not observed by Ichinose et al (10). Furthermore, previous studies have demonstrated an increase of sympathetic baroreflex sensitivity during mild levels of LBNP (11,15). The increased sympathetic baroreflex sensitivities observed during LBNP in the present study and others (11,15) are suggestive that alterations of sympathetic baroreflex sensitivity during orthostatic stress are important in the maintenance of orthostatic tolerance.…”
Section: Discussionsupporting
confidence: 35%
“…Consistent with prior studies (Crandall 2000;Ichinose et al 2004;Ogoh et al 2002Ogoh et al , 2003, the response of MAP to NP or NS was elicited slowly compared to that of HR (Figs. 2, 3, 4, 5).…”
Section: Discussionsupporting
confidence: 89%
“…The larger influence of arterial baroreflex on blood pressure maintenance during long-duration HDBR, even in the absence of evidence pointing to its enhancement, and the simultaneous reduction of the role of cardiopulmonary baroreflex can contribute toward the interpretation of the occurrence of syncope in individuals who have completed HDBR (20), or in astronauts upon return to earth. In addition, these conclusions could also be of importance in interpreting the pathology of subjects who are prone to syncope and orthostatic intolerance.…”
Section: Perspectives and Significancementioning
confidence: 99%